(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
The goal of this work is to study the operational characteristics of motor oils used in the engines of LW300FN Wheel Loaders, a typical example of construction and road-building transport equipment. Experimental studies were conducted on the operational characteristics of 15W-40 motor oil used in WEICHAI WP6G125E22 diesel engines (92kW) operating in heavily loaded conditions, such as quarry or construction sites. LW300FN Wheel Loaders are designed for continuous material handling under various, often severe, climatic and dusty environments.